2009
DOI: 10.1007/s00360-009-0384-y
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids in nestling Montagu’s harriers: variations according to age, sex, body condition and evidence for diet-related limitations

Abstract: Carotenoids are colored pigments forming the basis of many avian social traits. Before their utilization carotenoids must be acquired through diet and mobilized for specific uses. The relationships between carotenoid-based coloration, circulating carotenoids and body condition have been well studied in adult birds, but little is known in nestlings. Here, we investigated variations in carotenoid-based coloration in a raptor nestling, the Montagu's harrier (Circus pygargus), both in captivity and in natural cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 57 publications
4
54
0
Order By: Relevance
“…The carotenoid profile in plasma of predatory and scavenger raptors showed a predominance of xanthophylls (∼90%), especially lutein, and traces of other carotenoids [11], [12], [20], [43], [44]. In this study, we found an unexpectedly large variety of carotenoids in plasma of Andean condors and American black vultures, two scavengers that mostly feed on herbivore mammal carcasses in varying states of decomposition [24], [25], [30].…”
Section: Discussionmentioning
confidence: 73%
“…The carotenoid profile in plasma of predatory and scavenger raptors showed a predominance of xanthophylls (∼90%), especially lutein, and traces of other carotenoids [11], [12], [20], [43], [44]. In this study, we found an unexpectedly large variety of carotenoids in plasma of Andean condors and American black vultures, two scavengers that mostly feed on herbivore mammal carcasses in varying states of decomposition [24], [25], [30].…”
Section: Discussionmentioning
confidence: 73%
“…Juvenile birds can also convey condition via leg coloration, as in storks and raptors (Negro et al 2000, Casagrande et al 2009, Sternalski et al 2010, and the UV reflectance of nestling skin appears to be a signal that influences parental feeding (Jourdie et al 2004, Bize et al 2006. Juvenile American Coots (Fulica americana) display bright red skin on their head as well as orange feathers, which both appear to have evolved via parental favoritism for colorful chicks (Lyon et al 1994).…”
Section: Nestling Signals and Parental Investmentmentioning
confidence: 99%
“…about a week before fledging (note that some nests were fenced to protect them from harvesting activities, which also reduces predation risk before fledging). This pigment is involved in the immune response and birds with higher levels may be fitter (Sternalski et al 2010(Sternalski et al , 2012. Unexpectedly, the effect of mean breeding success was negative, meaning that juveniles experienced lower survival when born in years with higher mean breeding success (i.e.…”
Section: Both Breeding and Wintering Environments Contribute To Age-smentioning
confidence: 99%